PENERAPAN ETNOPARENTING BERBASIS NILAI BUDAYA SINTUVU SUKU KAILI DALAM MENGEMBANGKAN ASPEK SOSIAL EMOSIONAL ANAK DI KOTA PALU - Hikmaturrahmah, Hikmaturrahmah; Marwany (Pusat Studi Gender dan Anak, IAIN Palu, 2023)
Sintuvu cultural values in the reality of Kaili people's lives are extracted from various meaningful events as a learning process that forms awareness about togetherness. The value components that make up Sintuvu into the principle of togetherness and a symbol of unity in Kaili society include the values of harmony, kinship, the spirit of sharing, solidarity, consensus, responsibility and openness. From the results of initial observations on the ethnoparenting of the Kaili tribe in Palu City, it was found that the cultural values of the Kaili tribe, especially the cultural values of sintuvu are still not optimally applied in the people of Palu City, even feared to be increasingly displaced by western parenting patterns that are different from the values of local wisdom. As for Palu City as Kaili Land, of course, the most important thing in applying Kaili cultural values, one of which is Sintuvu cultural values. And Lere Village is one of the villages in Palu City where the majority of the population is Kaili tribe. So, the author is interested in conducting research on the application of Sintuvu cultural values of the Kaili tribe, with the research title